O bate-papo educacional: um gênero potencial para práticas sociais e atividades pedagógicas em aulas à distância - Reis, Susana Cristina dos (Linguagens & Cidadania, 2017)
Discussions about the process of teaching and learning online have been the focuses of different researches in the field of applied linguistics (Menezes, 2001; Warschauer,1996; Warschauer e Kern, 1998; Warshauer & Meskill, 2000; Tavares, 2001). In this article will be discussed how teachers beliefs and thoughts should be changed in order to work in an online environment. It also emphasizes the perspective of using genres in the classroom and specially digital genres to promote learner´s skills. At last, the educational chat will be analised and described as a genre which belongs to the system of online genres.Activities related to the use of the educational chat will be suggested as well as a potencial genre that can promote social practice and pedagogical tasks in a virtual classroom.